Partisipasi Petani dalam Program Jalan Usaha Tani (JUT) di Kecamatan Getasan Farmers' Participation in The Farmland Road Program in Getasan District - Santosa, Yoga; Prihtanti, Tinjung Mary (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
The Farmland Road Program (JUT) is a step taken by the government in providing infrastructure in agricultural areas. The JUT program requires community participation. Getasan District is one of the districts in Semarang Regency, Central Java Province, which received the JUT program in several hamlets. The purpose of this study was to identify the forms and stages of farmer participation in the JUT program and to identify the Arnstein ladder of participation in the JUT program in three hamlets in Getasan District. Respondents in this study were determined using a cluster sampling technique, namely dividing the population into several groups based on hamlets, then determining a quota in each hamlet of 20 farmers (a total of 60 farmers). Research data collection used survey techniques through interviews, observations, and documentation. The results of the study found that the highest form of participation was labor, and the highest stage of participation followed by respondents was at the JUT utilization stage. The results of the Arnstein ladder analysis found that the participation of the Ngaduman, Nglelo, and Tawang hamlets in the JUT program was at the placation level (5th ladder) in the Pseudo Participation category (tokenism ladder). Farmer participation in the JUT program, namely communication between the community and the government, is going well, but the government is still conducting a feasibility assessment.).